How do informal information sources influence women's decision-making for birth? A meta-synthesis of qualitative studies - Ruth A. Sanders; Kenda Crozier (BMC, 2018)
Abstract Background Women approach birth using various methods of preparation drawing from conventional healthcare providers alongside informal information sources (IIS) outside the professional healthcare context. An investigation of the forms in which these informal information sources are accessed and negotiated by women, and how these disconnected and often conflicting elements influence women's decision-making process for birth have yet to be evaluated. The level of antenatal preparedness women feel can have significant and long lasting implications on their birth experience and transition into motherhood and beyond. The aim of this study was to provide a deeper understanding of how informal information sources influence women's preparation for birth. Methods Seven electronic databases were searched with predetermined search terms. No limitations were imposed for year of publication. English language studies using qualitative methods exploring women's experiences of informal information sources and their impact upon women's birth preparation were included, subject to a quality appraisal framework. Searches were initiated in February 2016 and completed by March 2016. Studies were synthesised using an interpretive meta-ethnographic approach. Results Fourteen studies were included for the final synthesis from Great Britain, Australia, Canada and the United States. Four main themes were identified: Menu Birth; Information Heaven/Hell; Spheres of Support; and Trust. It is evident that women do not enter pregnancy as empty vessels devoid of a conceptual framework, but rather have a pre-constructed embodied knowledge base upon which other information is superimposed. Allied to this, it is clear that informal information was sought to mitigate against the widespread experience of discordant information provided by maternity professionals. Conclusion Women's access to the deluge of informal information sources in mainstream media during pregnancy have significant impact on decision making for birth. These informal sources redefine the power dynamic between women and maternal healthcare providers, simultaneously increasing levels of anxiety and challenging women's pre-existing ideations and aspirations of personal birth processes. A lack of awareness by some professionals of women's information seeking behaviours generates barriers to women-centred support, leaving an experience expectation mismatch unchecked. Trial registration CRD42016041491 17/06/16.